Automated nucleic acid extraction from whole blood, B. subtilis, E. coli, and Rift Valley fever virus on a centrifugal microfluidic LabDisk1. Issue 41 (7th May 2015) - Strohmeier, O.; Keil, S.; Kanat, B.; Patel, P.; Niedrig, M.; Weidmann, M.; Hufert, F.; Drexler, J.; Zengerle, R.; von Stetten, F.
<x xml:space="preserve">Abstract</x> We present total nucleic acid extraction from whole blood, Gram-positive Bacillus subtilis, Gram-negative Escherichia coli, and Rift Valley fever RNA virus on a low-cost, centrifugal microfluidic cartridge processed in a portable processing device.